Analysis of the Impact of Urban Sprawl on Groundwater Reserves in Kendari City Using Google Earth Engine (2000–2024) - Asramid Yasin (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
This study analyzes the impact of urban sprawl on groundwater reserves in Kendari City using the platform Google Earth Engine (GEE) with analysis period of 2000 and 2024. Urban sprawl is characterized by an increase in built-up land area estimated through the Normalized Difference Built-Up Index (NDBI), while groundwater reserves are projected through estimated baseflow groundwater runoff obtained from FLDAS ( Famine Early Warning Systems Network Land Data Assimilation System ) data. The results show a significant increase in NDBI values from 2000 to 2024, indicating a massive expansion of built-up areas. Conversely, baseflow values have decreased consistently, with the average baseflow decreasing from 0.00002685 kg/m²/s (2000) to 0.00001894 kg/m²/s (2024), reflecting pressure on the aquifer system due to reduced infiltration areas. Pearson correlation analysis revealed a significant weak negative effect between NDBI and baseflow in 2000 (r = -0.219; p-value = 0), which changed to a weak positive effect in 2024 (r = 0.126; p-value = 0), indicating a shift in hydrological dynamics due to the accumulated impacts of urbanization. This finding confirms that urban sprawl has reduced groundwater recharge capacity and threatened the sustainability of clean water supplies. The study recommends the need for sustainable spatial planning policies and groundwater conservation strategies to mitigate these negative impacts.